2019
DOI: 10.1037/cou0000349
|View full text |Cite
|
Sign up to set email alerts
|

The codevelopment of group relationships: The role of individual group member’s and other group members’ mutual influence and shared group environment.

Abstract: Although recent research has provided empirical support for the codevelopment of group interaction (defined as development in a common direction of perceptions of group relationships), no studies have yet investigated the "causes" of codevelopment among group members in the long term. The aim of the current study is to examine how the perceptions of an individual group member, and other group members, regarding group relationships influence each other over the course of treatment. We analyzed group data from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 45 publications
3
19
1
Order By: Relevance
“…The findings of the current study are also in line with the general perspective of a multidisciplinary approach to patients with chronic medical conditions, which suggest that implementing protocols based on both psychological and physical interventions could be beneficial (Conversano, 2019;Martino et al, 2019b). Improving patients' dispositional optimism and context sensitivity might be the novel target of mindfulness-based cognitive therapy (De Jong et al, 2016), peer-to-peer support (Callus and Pravettoni, 2018), and group therapies (Lo Coco et al, 2019), with the purpose of developing tailored psychological interventions in patients with chronic medical conditions (Conversano et al, 2019). The research in psychology is moving toward an increasingly patient-centered multidimensional approach, as recently debated within a psychodynamic perspective that highlighted the joint relevance of cognitive, emotional, and personality characteristics in the evaluation of clinical populations (Lingiardi et al, 2010;Hilsenroth et al, 2018;Lingiardi and McWilliams, 2018), with a peculiar concern on the link between aging and psychopathology (Del Corno and Kiosses, 2018).…”
Section: Discussionsupporting
confidence: 78%
“…The findings of the current study are also in line with the general perspective of a multidisciplinary approach to patients with chronic medical conditions, which suggest that implementing protocols based on both psychological and physical interventions could be beneficial (Conversano, 2019;Martino et al, 2019b). Improving patients' dispositional optimism and context sensitivity might be the novel target of mindfulness-based cognitive therapy (De Jong et al, 2016), peer-to-peer support (Callus and Pravettoni, 2018), and group therapies (Lo Coco et al, 2019), with the purpose of developing tailored psychological interventions in patients with chronic medical conditions (Conversano et al, 2019). The research in psychology is moving toward an increasingly patient-centered multidimensional approach, as recently debated within a psychodynamic perspective that highlighted the joint relevance of cognitive, emotional, and personality characteristics in the evaluation of clinical populations (Lingiardi et al, 2010;Hilsenroth et al, 2018;Lingiardi and McWilliams, 2018), with a peculiar concern on the link between aging and psychopathology (Del Corno and Kiosses, 2018).…”
Section: Discussionsupporting
confidence: 78%
“…Our findings are consistent with other studies from general population that have found beneficial influence of participation in participatory action research using Photovoice on emerging young adults ( 57 , 58 ), particularly in terms of perceived support ( 75 ). The participatory and group-based approach seems to be a means of fostering a sense of belonging, particularly through the recognition of experiential knowledge ( 25 , 39 ), and subsequently improving the perception of social support through exchanges between group members ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, at this age, youth tend to associate more closely with people who share their interests (e.g., sports, community, peer group, volunteering) and with whom they feel a connection ( 37 ). Social interactions can greatly influence their sense of social belonging, through regular encounters with their friend group, the affects generated ( 38 ), the ability for the individual to name their expectations and fears, and the development of a shared language ( 39 ). The role of the romantic partner should also be a factor to consider, at a time when love life is gradually becoming more important to many youth ( 36 , 40 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is substantial evidence that group treatment is effective with several disorders (Burlingame et al, 2018b , Burlingame, McClendon & Alonso, 2011 ; Burlingame et al, 2013 ), the underlying mechanisms by which patient change is achieved have several challenges. There is a structural complexity in the group relationship which may represent a challenge when investigating its development over time (Lo Coco, Gullo, Di Fratello, Giordano, & Kivlighan, 2016a ; Lo Coco et al, 2019a ). An individual group member develops a therapeutic relationship with the therapist, but also with the other group members and with the group-as-a-whole and most of previous research did not address this structural complexity by focusing mainly on the relationship between therapist and patient in the group (Lo Coco, Gullo & Kivlighan, 2012 ).…”
Section: Introductionmentioning
confidence: 99%